Assessment and Development of Global Leadership Competencies in the Workplace: A Review of Literature. (August 2016) - Cumberland, Denise M.; Herd, Ann; Alagaraja, Meera; Kerrick, Sharon A.
The Problem: In the 21st century, globalization is key. Therefore, assessing and developing global leadership competencies is an important topic in human resource development (HRD). Global leadership competencies encompass personality traits, knowledge, and skills, as well as behaviors. While there has been a plethora of scholar-practitioner literature identifying global leadership competencies, there has been far less focus on assessing global leadership competencies and how these competencies are developed. The Solution: We attempt to address this gap by examining the state-of-the-art literature on global leadership assessment and development from several disciplines, including HRD, management, and leadership. With regard to global leadership competency assessment, our goal is to synthesize the literature and provide HRD professionals with a systematic method for identifying instruments that measure core global competencies. With regard to global leadership development, our aim is to provide a framework for understanding how global leadership competencies can be developed. The Stakeholders: The identification and categorization of various instruments that measure global competencies, as well as a framework that outlines methods to develop these competencies, will benefit human resource (HR) professionals and HRD practitioners.